PERKEMBANGAN BAHASA ANAK USIA 4-5 TAHUN DITINJAU DARI ASPEK FONETIK DAN ASPEK SEMANTIK - Anisa Wiwin Handayani Anisawwn; Anita Chandra; Joko Sulianto (UIR PRESS, 2022)
Language Development Children aged 4-5 years are basically able to pronounce conversations correctly and are able to say what they want. However, in the daily life of children aged 4-5 years, there are those who have delays in language development or are less clear in the pronunciation of letters. The purpose of this study is that researchers want to examine the language development of children who experience delays with the method of phonetic and semantic stages. The method used by the researcher is classroom action with a variety of role-playing and sound playing. The results of the study indicate that the language of RR has significant increase, namely, RR is willing to communicate with his peers and pronounces the letter S clearly.